Penerapan Social-Commerce dan Standar Perlindungan Data Pribadi Menurut Hukum Positif Indonesia - Achmad Awaluddin Mughni; Kevin Laksmana Putri (Jurnal Hukum Lex Generalis, 2025)
Along with the times, E-commerce develops hand in hand with social media. Social media, which was originally a means of entertainment, has transformed into a multipurpose platform that contains social media (entertainment) and shopping (shopping) and even completing payments, which is commonly called social commerce. social commerce provides many benefits to users, but it also threatens the sustainability of micro, small and medium enterprises (MSMEs). This happens because MSMEs with limited capital will lose to entrepreneurs with large capital from other countries. Large entrepreneurs can minimize prices because their production is large, while MSMEs are still limited. This allows online sellers to prefer to market goods from large entrepreneurs rather than MSMEs. The security of users' personal data is also a concern because social commerce contains personal data to bank accounts for payment. The purpose of this research is to answer the Application of social-commerce and Personal Data Protection Standards According to Indonesian Positive Law. The type of research used is normative legal research. The result of this research is that social commerce can be applied in Indonesia if it has met the requirements in accordance with the Regulation of the Minister of Trade Number 31 of 2023 concerning Business Licensing, Advertising, Guidance, and Supervision of Business Actors in Electronic Commerce and Personal Data Protection Standardization can provide a guarantee of fulfilling the rights of personal data subjects in accordance with Law Number 27 of 2022 concerning Personal Data Protection.